Hubungan Ketepatan Kode Diagnosis Terhadap Status Klaim JKN Rawat Inap di Rumah Sakit Pelabuhan Jakarta - Amanda, Rizkia; Sonia, Dina (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2023)
The accuracy of determining the diagnosis code is necessary for the benefit of patient health information in carrying out health services. The accuracy of the diagnosis code is also required for the benefit of claiming National Health Insurance (JKN). The research aims to determine the correlation between the accuracy of the diagnosis code and the status of inpatient National Health Insurance (JKN) claims. The research method was an inferential analysis with a cross-sectional research design using the chi-square statistical test. The samples of the research were 125 medical records. Samples were taken by way of proportional stratified random sampling. Based on the research results, the accuracy of determining the diagnosis code was 114 (91,2%) while the inaccuracy of determining the diagnosis code was 11 (8,8%). JKN claims received were 104 (83,2%) while JKN claims that were postponed were 21 (16,8%). The results of the chi-square statistical test obtained odd ratio value of 20,7, meaning that the correct diagnosis codes has 20,7 times chance of JKN claims approval than the incorrect diagnosis codes. The significance value obtained of 0.000. The p-value shows <0.05, so Ho is rejected and Ha is accepted or there is a correlation between the accuracy of the diagnosis code and the status of inpatient JKN claims at the Pelabuhan Jakarta Hospital. This research concludes that there is a correlation between the accuracy of the diagnosis code and the status of inpatient JKN claims.